Researcb on tbe Anti Interference Antenna Tecbnology of tbe Limited Electromagnetic Conductor Surface - Bocun Deng; Jianjun Shen; Xiangdong Xu (Dianxin kexue)
The prob1em of e1ectromagnetic interference of 2 400 MHz band were studied， based on the physica1 1ayer microstrip techno1ogy， combining the e1ectromagnetic finite conductor surface mirror and array factor superposition princip1e. Antenna structure which having specia1 radiation performance was designed，the antenna medium was studied. Through the examination on the antenna， the anti interference performance was verified. It has an effect on the reducing of the channe1 packet retransmission rate and the increasing of the channe1 packet transmission rate.